Classification of 7-dimensional einstein nilradicals - Fernández Culma, Edison Alberto (2012)
The problem of classifying Einstein solvmanifolds, or equivalently, Ricci soliton nilmanifolds, is known to be equivalent to a question on the variety N n(ℂ) of n-dimensional complex nilpotent Lie algebra laws. Namely, one has to determine which GL n(ℂ)-orbits in N n(ℂ) have a critical point of the squared norm of the moment map. In this paper, we give a classification result of such distinguished orbits for n = 7. The set N 7(ℂ)/GL 7(ℂ) is formed by 148 nilpotent Lie algebras and 6 one-parameter families of pairwise non-isomorphic nilpotent Lie algebras. We have applied to each Lie algebra one of three main techniques to decide whether it has a distinguished orbit or not.